2017
DOI: 10.18632/oncotarget.18960
|View full text |Cite
|
Sign up to set email alerts
|

Association between 8q24 rs6983267 polymorphism and cancer susceptibility: a meta-analysis involving 170,737 subjects

Abstract: Published data on the association between 8q24 rs6983267 polymorphism and cancer risk are inconsistent. Thus, we conducted a meta-analysis to evaluate the relationship between rs6983267 polymorphism and cancer risk. We searched on PubMed, EMBASE, Web of Science and China National Knowledge Infrastructure (CNKI) up to November 1, 2016 for relevant studies. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the strength of this association. We included 78 case-control studies with a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…This association between 8q24 and risk for thyroid cancer and other cancers (prostate cancer, colorectal cancer, breast cancer, etc. ), has been confirmed in recent studies [ 105 , 106 ].…”
Section: Non-syndromic Familial Non-medullary Thyroid Carcinoma (Nsfnsupporting
confidence: 70%
“…This association between 8q24 and risk for thyroid cancer and other cancers (prostate cancer, colorectal cancer, breast cancer, etc. ), has been confirmed in recent studies [ 105 , 106 ].…”
Section: Non-syndromic Familial Non-medullary Thyroid Carcinoma (Nsfnsupporting
confidence: 70%
“…Numerical abnormalities of CTCs can be divided into different subtypes, such as triploidy, tetroploidy and multiploidy. Previous studies have shown that CEP 8 reflects numerical chromosomal abnormalities, which have been reported in thyroid cancer, and lung, esophageal, gastric and colon cancers [27][28][29]. Thus, aneuploidy of CEP 8 examined by CEP8-iFISH can be used to detect CTCs.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, an increasing number of studies have confirmed that lncRNA CCAT2 SNPs are associated with susceptibility to multiple diseases. For example, rs6983267 polymorphisms are associated with significantly increased risk for prostate cancer in Asians (Zhu et al, ) and increased the susceptibility of ovarian cancer in Han Chinese women (Han et al, ). However, some other studies have revealed that rs6983267 showed a negligible association with breast cancer risk (Y. Zhang et al, ), and He et al () did not find a significant association between rs6983267 polymorphism and gastric cancer risk in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%